The Role of Guru Penggerak in Program Merdeka Belajar at Junior High School - Ahmad Hafiz Pratama; Machdalena Vianty; Rita Inderawati (Jurnal Pendidikan Indonesia, 2024)
Many teachers need help improving 21st-century skills in students. This research aims to analyze the role of the Driving Teacher in teaching the Independent Learning Program, as well as the factors that support and hinder this role. This type of research is qualitative. The methods used to collect data are observation, interviews, and documentation. The data collection instrument uses a questionnaire. The data analysis technique uses qualitative data analysis. The research results show that the Independent Learning Program is part of the Independent Curriculum (Independent Curriculum) and the Teacher Mobilization Program. Second, the Mobilizing Teacher initiates the Independent Learning Program in the classroom and collaborates with fellow teachers to align the program with the curriculum. Third, teachers should be motivated as initiators, facilitators, and inspirers, and other teachers should be educated to create student-friendly programs. Fourth, teachers motivate students by building confidence in the class and providing learning motivation. Fifth, the Activation Teacher provides support to students in overcoming difficulties. Sixth, they adapt learning to each student's needs, utilizing available resources. Seventh, the Driving Teacher evaluates student progress through reflection and feedback. Teachers integrate the Independent Learning Program with the school curriculum, design lessons, and collaborate with other parties to ensure alignment.